2003
DOI: 10.1007/s00221-003-1504-7
|View full text |Cite
|
Sign up to set email alerts
|

Target and hand position information in the online control of goal-directed arm movements

Abstract: The present study compared the contribution of visual information of hand and target position to the online control of goal-directed arm movements. Their respective contributions were assessed by examining how human subjects reacted to a change of the position of either their seen hand or the visual target near the onset of the reaching movement. Subjects, seated head-fixed in a dark room, were instructed to look at and reach with a pointer towards visual targets located in the fronto-parallel plane at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
112
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(130 citation statements)
references
References 44 publications
14
112
0
4
Order By: Relevance
“…This finding is all the more striking because control of hand orientation during reaching could be prone to execution errors due to inaccuracies in outgoing motor commands and to passive mechanical perturbations of the hand away from its desired orientation. Our findings are consistent with other studies that suggested a role for proprioception in the on-line correction of hand direction and distance in response to visual perturbations of target or hand position (Sarlegna et al, 2003(Sarlegna et al, , 2004Bagesteiro et al, 2006).…”
Section: Proprioceptive Integration For Perception Action and On-lisupporting
confidence: 93%
“…This finding is all the more striking because control of hand orientation during reaching could be prone to execution errors due to inaccuracies in outgoing motor commands and to passive mechanical perturbations of the hand away from its desired orientation. Our findings are consistent with other studies that suggested a role for proprioception in the on-line correction of hand direction and distance in response to visual perturbations of target or hand position (Sarlegna et al, 2003(Sarlegna et al, , 2004Bagesteiro et al, 2006).…”
Section: Proprioceptive Integration For Perception Action and On-lisupporting
confidence: 93%
“…In both situations, the large, consciously perceived target displacements resulted in arm movement corrections initiated with a similar latency. This latency, within the range of values reported previously (Georgopoulos et al, 1981;Sarlegna et al, 2003), presumably reflects voluntary rather than automatic modifications of the initial motor plan (Day and Lyon, 2000;Desmurget et al, 2004;Johnson and Haggard, 2005). We interpret the lack of grasp/no grasp difference as possible evidence that the predictive mechanisms engaged in the control of grip force are low-demanding processes.…”
Section: Is Predictive Grip Force Control a Demanding Process?supporting
confidence: 83%
“…This paradigm was selected because it elicits fast motor corrections that allow reaching the displaced target before movement offset (Day and Brown, 2001;Prablanc et al, 2003;Sarlegna et al, 2003). An original feature of the present study was that arm movements had to be performed while holding an object.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the control of movement distance is mainly based on proprioceptive signals and less on visual information, which is regarded as more important for the control of movement direction (Sainburg et al, 2003;Sarlegna et al, 2003;Bagesteiro et al, 2005). This is consistent with the evidence that these two parameters seem to be specified separately in the brain (Flanders et al, 1992;Lacquaniti et al, 1995;Georgopoulos, 2000).…”
Section: Influence Of Hand Position On Reaching-related Activitysupporting
confidence: 79%